Experimental and Computational Study of Acceleration Response in Layered Cylindrical Structure Considering Impedance Mismatch Effect - Sachiko Sueki; Samaan G. Ladkany; Brendan J. O’Toole (Shock and Vibration)
Electronic devices, especially those having high performance capabilities, are sensitive to mechanical shocks and vibrations. Failure of such devices in smart projectiles caused by vibrations has been observed. The currently accepted methodology to protect electronic devices in smart projectiles is use of stiffeners and dampers. However these methods are not effective in protecting the electronic devices from high frequency accelerations in excess of 5,000 Hz. Therefore, it is important to find more effective methods to reduce high frequency vibrations for smart projectiles. In this study, layered cylindrical structures are studied experimentally and computationally to understand the effect of impedance mismatch in axial acceleration response under an impact loading. Experiments are conducted by applying impact forces at one end of cylindrical structures and measuring accelerations at the other end. Experimental results suggest that high frequency accelerations in layered structures could be less compared to those in homogeneous cylinders if a returning wave from the end of the projectile does not interfere with the applied impact force. Computational studies using finite element analysis (FEA) verified the experimental results of our interference hypothesis.